Pola Pemberdayaan Ekonomi Generasi Milenial (Studi Kasus Komunitas Serikat Saudagar Nusantara (SSN) Di Medan) - Neila Susanti; M Marliyah (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2019)
Millennials or often called Generation Y is a term used to refer to generations born in the 1980s to 2000. This generation is familiar with communication, media, and digital technology. Not surprisingly, this generation is taking advantage of technological advances as an opportunity to do business. This phenomenon was exploited by Rendy Saputra to establish the Community of Saudagar Nusantara (SSN) Society. The activities carried out by the SSN community are interesting to study because in a short time (established 2 June 2017) this community was able to mobilize various communities in 40 cities in Indonesia as partners in empowering MSMEs. This study aims to determine the pattern of economic empowerment carried out by Medan SSN and SWOT analysis of the empowerment carried out. This research is descriptive qualitative with indepth interview as an instrument for collecting data. The results showed that the pattern of empowerment carried out by Medan SSN was Mentoring Bisnis Pekanan (MBP) Program, Kopdar Saudagar Nusantara, SSN and visiting business of member and non-member SSN, and Group WhatsApp for communication, business promotion, and sharing knowledge through online lectures. Based on the value of Internal Strategy Factors (IFAS) and External Strategy Factors (EFAS), SSN Medan is known that the pattern of empowerment carried out by Medan SSN is in the first quadrant, which supports progressive strategies.